Constitutional Court, Judicial Independence, and Efforts to Achieve Qualified Justice - Irfan Nur Rachman (Hasanuddin Law Review, 2019)
Judicial Corruption is a disgrace to the world of justice and disaster for the justice seeker community. The judiciary is the third branch of state power after the executive and legislature. The judicial function is as a control and a counterweight to both branches of the power so as not to fall into arbitrary acts. In other words, the judiciary basically serves to implement the principle of checks and balances. However, if the justice functioning as a counterweight is actually involved in the vortex of judicial corruption that has plagued the judicial institutions, then what happens is the absence of justice because the judicial institution becomes unqualified and degrades its reputation in the public eye. This will lead to a vote of no confidence in the judiciary as a whole and the community has the potential to seek justice in other ways that may be done in illegal ways. Therefore, it is important to realize quality judiciary by organizing institutional aspects, the process of recruitment of constitutional justices, and producing decisions containing new legal breakthroughs, so that will be realized a qualified judicial institution.